PENDIDIKAN ANTIKORUPSI DI LINGKUNGAN KELUARGA: MENCIPTAKAN TELADAN DARI RUMAH - Suhari, Suhari; Lestari, Bernadetta Budi; Listyaningsih, Listyaningsih; Ardhana, Nehru Firdaus; Widoyo, Salsa Dea Ananda (Jurnal Abdimas Bina Bangsa, 2025)
Efforts to create role models from home in the context of implementing Anti-Corruption Education today are very important to implement because the family is the foundation for the formation of anti-corruption awareness and integrity. To increase awareness of the role of the family in Anti-Corruption Education, the PPKn Lecturer Team of PGRI Adi Buana University Surabaya and the PPKn Lecturer Team of Surabaya State University carried out Community Service at LLDIKTI Region VII East Java, especially for the Dharma Wanita Persatuan Mothers which was attended by 28 participants consisting of 7 administrators and 21 members. The series of activities included: pre-test, presentation, discussion, simulation, question and answer, and post-test. The results of the pre-test and post-test showed an increase in participants' understanding of anti-corruption and integrity. The next hope is to increase the role of the family in the formation of anti-corruption behavior through role models formed from the family environment, then a commitment to implementing it in the practice of life in society and on a wider scale in national life